Men and Women of Parapsychology, Personal Reflections, Esprit Volume 2 edited by Rosemarie Pilkington - Potts, Michael (Journal of Scientific Exploration, 2014)
In recent years a number of books have been published that offer short autobiographical essays of academics, focusing on their research and how their life history affected their scholarly development. These could be labeled as "intellectual journey narratives." Some volumes focus on philosophers and their religious faith or lack thereof (e.g., Clark, 1997, Antony, 2007). Psychology has its own version of the intellectual journey narrative, in T. S. Krawiec's (1972, 1974, 1978) multivolume set of autobiographical essays by contemporary psychologists. In 1987, Rosemary Pilkington edited her first volume of essays entitled Men and Women of Parapsychology: Personal Reflections, Esprit Volume 1. It contains autobiographical essays by Jule Eisenbud, Montague Ullman, Jan Ehrenwald, Eileen Coly, Joseph H. Rush, Gertrude R. Schmeidler, Emilio Servadio, Renée Haynes, Hans Bender, Karlis Osis, George Zorab and Bernard Grad. The second (2013) volume contains autobiographical essays by Mary Rose Barrington, Eberhard Bauer, William Braud (now deceased), Stephen Braude, Richard S. Broughton, Larry Dossey, Sally Rhine Feather, Erlendur Haraldsson, Arthur Hastings, Stanley Krippner, Lawrence LeShan, Roger Nelson, John Palmer, Guy Leon Playfair, William G. Roll (now deceased), Serena Roney-Dougal, Stephan A. Schwartz, Rex G. Stanford, Russell Targ, Charles T. Tart, and Walter von Lucadou. Between the two volumes almost every significant contemporary parapsychologist is represented, with the major exceptions being the late John Beloff and the late Ian Stevenson.